Islamic Religious Learning In Providing Understanding Of Radical Hazards Based On Affection Approach (Study on Islamic religious Subjects at Junior High School) - Kusen Kusen (Institut Agama Islam Negeri (IAIN) Curup, 2017)
The word Islam and radical, is a familiar word to hear, even in many of the recent events carried out by a group of people who in the name of Islam. Understanding the radical concept has penetrated into various elements, included in education. In responsing to this, the goverment have to take an action through reorganizing the existing materials in Islamic lesson which is taught in educational institutions. Rearrangement of islamic lesson is important. Because the existing material had proved that its inadequate to bear students who are tolerant, moderate, and inclusive. The proof can be seen from the number of terrorist and Islamic radicalism which is involving educated young people, both students, college students, or college graduates. Moreover, lately, there has been a tendency of systematic efforts by certain denominations to teach extreme ideological loyalist of religious doctrine among learners. This paper tries to provide an understanding which related to radical concepts on the explanation of Islamic lesson materials in junior high school. So that, learners can understand more about the concept of islam which is peaceful not violence. One of the strategy in providing a radical understanding among learners is to develop Islamic lesson materials through compassion-based learning.